2017
DOI: 10.1007/s11356-017-9240-x
|View full text |Cite
|
Sign up to set email alerts
|

The environmental risks of neonicotinoid pesticides: a review of the evidence post 2013

Abstract: Neonicotinoid pesticides were first introduced in the mid-1990s, and since then, their use has grown rapidly. They are now the most widely used class of insecticides in the world, with the majority of applications coming from seed dressings. Neonicotinoids are water-soluble, and so can be taken up by a developing plant and can be found inside vascular tissues and foliage, providing protection against herbivorous insects. However, only approximately 5% of the neonicotinoid active ingredient is taken up by crop … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
263
2
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 474 publications
(274 citation statements)
references
References 133 publications
(282 reference statements)
7
263
2
2
Order By: Relevance
“…Since human health has been a matter of primary concern so many studies which have so far been done arrived at the conclusion that pesticide exposure is associated with chronic health ailments . These primarily include dermatologic, respiratory, memory disorders like neurodeficits, birth defects and miscarriages . Moreover, bioaccumulation of pesticide residues show an association to cause cancer, depression, seizure disorder, liver and kidney dysfunction .…”
Section: Introductionmentioning
confidence: 99%
“…Since human health has been a matter of primary concern so many studies which have so far been done arrived at the conclusion that pesticide exposure is associated with chronic health ailments . These primarily include dermatologic, respiratory, memory disorders like neurodeficits, birth defects and miscarriages . Moreover, bioaccumulation of pesticide residues show an association to cause cancer, depression, seizure disorder, liver and kidney dysfunction .…”
Section: Introductionmentioning
confidence: 99%
“…When directly applied to crops (typically as a seed treatment) or as contamination of wildflowers, this can result in low-level contamination of nectar and pollen at concentrations in the parts per billion (ppb), providing a direct route of exposure to foraging bees [6,18]. An increasing number of studies investigating the effects of neonicotinoid exposure on bees have reported detrimental impacts on a range of behaviours [1921], including individual foraging performance, which could impair colony development in social bees [22,23].…”
Section: Introductionmentioning
confidence: 99%
“…No clear dose response was evident from these results; 7 µg/g produced no significant effects, and 8 µg/g did not significantly alter eclosion or butterfly mass. By comparison, in Wood and Goulson () the highest concentration of clothianidin was detected in maize pollen that was previously treated with neonicotinoids (36.88 ng/g), yet only 4 ng/g was detected on nontreated wildflowers occurring along roadside ditches near feed yards in the Southern High Plains (Peterson et al ). Reported 24‐h median lethal concentration values for clothianidin ranged from 2400 to 186 000 ng/g among 3 agricultural crop pest moths (Botías et al ; Wood and Goulson ).…”
Section: Discussionmentioning
confidence: 96%
“…By comparison, in Wood and Goulson () the highest concentration of clothianidin was detected in maize pollen that was previously treated with neonicotinoids (36.88 ng/g), yet only 4 ng/g was detected on nontreated wildflowers occurring along roadside ditches near feed yards in the Southern High Plains (Peterson et al ). Reported 24‐h median lethal concentration values for clothianidin ranged from 2400 to 186 000 ng/g among 3 agricultural crop pest moths (Botías et al ; Wood and Goulson ). However, crop pest species may not be reliable indicators of clothianidin toxicity among pollinators because multiple generations have been exposed to pesticides, possibly eliciting resistance (Wood and Goulson ).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation